Assessment of axial load carrying capacity of GFRP funicular shells with steel mesh. (April 2020) - Bashir, Khalid; Ahad, Arif; Sachithanantham, P.; Haque Chaudhuri, Chaidul
Abstract: This paper presents the test results of an experimental program to investigate the load-bearing capacity of twenty-seven Glass Fibre Reinforced Polymer GFRP funicular shells under pure compression load. The test parameters include the number of glass fiber layers, the rise of shells and the effect of inclusion of steel mesh as an additional reinforcement to the glass fiber. Comparisons between the experimental test results of various parameters are performed in terms of the ultimate load-carrying capacity. A parametric study was conducted which showed the significant effect of the increasing rise on the load bearing capacity of GFRP shells. In general, the results of this study revealed that the ultimate load-carrying capacity gets increased by nearly 58% by increasing the number of normal glass fiber layers from two to four. Moreover, an increase in the ultimate load-carrying capacity of nearly 15% to 26% was observed with the inclusion of steel mesh as an additional reinforcement to the glass fiber. In the latter case, the deflections were comparatively lesser than the former. The failure loads of all the specimens were found and two equations were proposed to express the relation between rise, span to rise ratio, with ultimate load. It is concluded that the ultimate loads are a function of the rise of the shell and the number of fiber layers. The addition of steel mesh increases stiffness of shells, there by reduces total deflection.